2017
DOI: 10.7860/jcdr/2017/24961.10544
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Patients’ Rights among Inpatients of a Tertiary Care Teaching Hospital– A Cross-sectional Study

Abstract: Introduction: The rights of a patient are a set of rules of conduct which govern the interaction between the patients' and healthcare professionals. Every patient has a right to be informed about their rights and also the responsibility of the healthcare provider.Aim: To assess awareness among inpatient about patients' rights at an academic accredited hospital. Materials and Methods:A questionnaire based cross-sectional study was carried out among 350 patients admitted to the wards of a Tertiary Care Teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 10 publications
8
32
0
1
Order By: Relevance
“…So, the mean score of observing patient’s rights in the participants with academic education level was more than other participants. This finding is consistent with results of previous studies (Agrawal et al , 2017; Halawany et al , 2016; Abedi et al , 2017). With a low educational level, the patients’ knowledge and awareness of their rights also decreases.…”
Section: Discussionsupporting
confidence: 94%
“…So, the mean score of observing patient’s rights in the participants with academic education level was more than other participants. This finding is consistent with results of previous studies (Agrawal et al , 2017; Halawany et al , 2016; Abedi et al , 2017). With a low educational level, the patients’ knowledge and awareness of their rights also decreases.…”
Section: Discussionsupporting
confidence: 94%
“…Abedi et al also indicated the need to increase patients’ awareness of their rights during the delivery of healthcare services [ 28 ]. As stated by Agrawal et al, to take effective educational measures to improve general awareness not only among patients but also among various stakeholders in the healthcare system, it is important to assess the awareness of hospitalized patients of their rights [ 29 ]. As shown by the results of a study conducted by Tabassum et al in two hospitals in Lahore (Pakistan) from the public and the private sectors, most patients (64%) were not aware of their rights.…”
Section: Discussionmentioning
confidence: 99%
“…22 40 41 Patient rights movements and civil society organisations arguing for improved accountability in healthcare are gathering momentum across the globe and more so in LMICs. 40 Although the rhetoric on patient rights is burgeoning, empirical research in this area is nascent and most of the existing research studies [42][43][44][45] limit themselves to studying awareness of patient rights. Also, the available frameworks in the literature identify the typology of patients rights 8 and a few other attempt to situate the patients rights within the larger human rights framework.…”
Section: Rationalementioning
confidence: 99%